# sinz=z , z=x+iy

### 1 Answer | Add Yours

sin w=z

sin w=((e^{iw}-e^{iw})/(2i))

e^{iw}-e^{-iw}=2iz multiply everything by e^{iw}

e^{2iw}-1=2ize^{iw}

e^{2iw}-2ize^{iw}-1=0

y=e^{iw}

y²-2izy-1=0

y=((2iz±√((-2iz)²-4(-1)))/2)=((-iz±√(-4z²+4))/2)

e^{iw}=-iz±√(1-z²) so our answer is

iw=ln(-iz±√(1-z²))

w=(1/i)ln(-iz±√(1-z²))+2πn

I do not see an easy way to solve this equation for z.

z=0 is an obvious solution.

Using newton's method on the original function

f(z) = sin(z)-z

f '(z) = cos(z) - 1

Pick a x_0 and iterate the following formula

x_(n+1) = x_n - f(x_n)/f '(x_n)

I get z = 7.4976763 - 2.7686783 i as one posible answer from about 10 iterations starting with (5+5i)

z = 13.899960 - 3.3522099 i is another answer.

I do not see a pattern, but perhaps you can...